Peculiarities of the classification of raw-smoked sausages during forensic commodity examination - Ye. М. Sobakar; Ya. О. Kulyk (Bulletin of Kharkiv National University of Internal Affairs)
The main identification tasks of commodity examination of raw-smoked sausages are establishing their authenticity, determining compliance with safety and quality standards. To achieve these tasks, forensic experts conduct a number of studies and determinations, which include determining the composition of the product, determining the composition, quality and quantity of components, determining compliance with quality standards, as well as determining the content of atypical impurities and impurities. Carrying out these identification tasks, the examination allows to ensure the quality and safety of the product and forms the protection of consumer rights. Defects in raw-smoked sausages can occur for a variety of reasons and are usually the result of deficiencies in production, storage, or transportation.